Fast coding unit partitioning method based on edge detection for HEVC intra-coding. Issue 5 (July 2016) - Belghith, Fatma; Kibeya, Hassan; Ben Ayed, Mohamed; Masmoudi, Nouri
Abstract High efficiency video coding (HEVC) standard is the latest video coding standard generation. It employs powerful coding tools to obtain improved compression efficiency. To better exploit the redundancies, HEVC adopts a very flexible quad-tree coding structure, allowing the encoder to use a block partition that matches the image features. This exhaustive technique may achieve a higher coding efficiency; however, it induces a significant computational complexity in the encoding engine. This paper proposes a new texture parameter for classifying digital videos as a first contribution and then introduces an efficient coding unit (CU) partitioning algorithm based on the early defined texture parameter in order to speed up the encoding process. In fact, the proposed technique is based on edge detection by performing SOBEL filtering in order to decide the appropriate CU size. Compared to the original HEVC, the average execution time-saving is about 31 % while maintaining almost the same output video quality.